Understanding Why Postpericardiotomy Syndrome is More Common after Surgical Atrial Septal Defect Closure: A Sneak Peek at Atrial Functions by Speckle-tracking Echocardiography - AbdelMassih, Antoine Fakhry; Haidar, Wafaa; AlAbid, Sarah; AttAllah, Theodora; Khraisat, Bann; Khan, Arshad; Hafez, Beshr (Journal of the Practice of Cardiovascular Sciences, 2025)
Abstract Postpericardiotomy syndrome (PPS) involves the development of pericardial and pleural effusion following open cardiac surgery. To date, it is not completely understood why it is more likely to develop after atrial septal defect closure. This case-based brief report describes a discrepancy in the conduit and reservoir components of atrial functions by speckle-tracking echocardiography (STE) in a case following atrial septal defect (ASD) closure compared to another case who had a repair of the mitral cleft. This finding was associated with a mild effusion developing in ASD postoperative case. Despite the limited proofs brought by these two cases, it should encourage the implementation of larger cohort studies, testing atrial functions by STE, in patients after ASD closure, and calculating the diagnostic accuracy of different components of atrial functions in predicting PPS development.